2022
DOI: 10.1021/acsinfecdis.2c00346
|View full text |Cite
|
Sign up to set email alerts
|

Human B Cell Epitope Map of the Lyme Disease Vaccine Antigen, OspA

Abstract: The Lyme disease (LD) vaccine formerly approved for use in the United States consisted of recombinant outer surface protein A (OspA) from Borrelia burgdorferi sensu stricto (ss), the bacterial genospecies responsible for the vast majority of LD in North America. OspA is an ∼30 kDa lipoprotein made up of 21 antiparallel β-strands and a C-terminal α-helix. In clinical trials, protection against LD following vaccination correlated with serum antibody titers against a single epitope near the C-terminus of OspA, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 79 publications
2
33
0
Order By: Relevance
“…HX-MS provides peptide level resolution of antibody-antigen interactions in solution based on differential hydrogen-deuterium exchange rates between unbound and bound targets (Angalakurthi et al, 2018; Brier et al, 2021; Chen et al, 2019; Grauslund et al, 2021; Hodge et al, 2022; Malito et al, 2013; Seow et al, 2022; Vinciauskaite and Masson, 2022). We recently used HX-MS to localize a dozen human B cell epitopes the B. burgdorferi antigen, OspA (Haque et al, 2022). In the case of OspC, we first generated a peptidic map of OspC A , which yielded 87 peptides that covered the entire length of the molecule ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HX-MS provides peptide level resolution of antibody-antigen interactions in solution based on differential hydrogen-deuterium exchange rates between unbound and bound targets (Angalakurthi et al, 2018; Brier et al, 2021; Chen et al, 2019; Grauslund et al, 2021; Hodge et al, 2022; Malito et al, 2013; Seow et al, 2022; Vinciauskaite and Masson, 2022). We recently used HX-MS to localize a dozen human B cell epitopes the B. burgdorferi antigen, OspA (Haque et al, 2022). In the case of OspC, we first generated a peptidic map of OspC A , which yielded 87 peptides that covered the entire length of the molecule ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…OspC A and B5 MAb were buffer exchanged and assayed by our previous protocol (Haque et al ., 2022). Previously flash frozen OspC A (19μM) was thawed at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the HEXITOPE algorithm vs X-ray crystallography has previously been established (Toth et al., manuscript in preparation), including with the antibody–antigen systems used in this study . The goal of this work is to establish the accuracy of the screening HX protocol vs complete HX.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In our previous study, we reported epitope mapping of OspA with a range of mAbs by complete HX. In the present study we have selected two mAbs (212-55 and 3-24) to validate our screening HX method.…”
Section: Methodsmentioning
confidence: 99%